Między Kijowem a Konstantynopolem Relacje Kościoła ukraińskiego z Patriarchatem Ekumenicznym (X–XXI w.) - Kuczara, Konrad (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
Relations between the Ukrainian Church and Constantinople were difficult. This goes back as far as 988, when the Christianisation of the Rus created a strong alliance between Kiev and the Byzantine Empire. There were times when Constantinople had no influence over the Kiev Metropolis. During the Mongolian invasion in 1240, the Ukranian region was broken up and Kiev lost its power. The headquarters of the Kiev Metropolis were first moved to Wlodzimierz nad Klazma in 1299 and then to Moscow in1325. In 1458 the Metropolis of Kiev was divided into two; Kiev and Moscow, but Kiev still remained under the jurisdiction of the Patriarchate of Constantinople. Since that time, the orthodox hierarchs of Moscow no longer adhered to the title Bishop of Kiev and the whole of Rus and in 1588 the Patriarchate of Moscow was founded. In 1596 when the Union of Brest was formed, the orthodox church of the Polish Lithuanian Commonwealth was not liquidated. Instead it was formally revived in 1620 and in 1632 it was officially recognized by king Wladyslaw Waza. In 1686 the Metropolis of Kiev which until that time was under the Patriarchate of Constantinople was handed over to the jurisdiction of Moscow. It was tsarist diplomats that bribed the Ottoman Sultan of the time to force the Patriarchate to issue a decree giving Moscow jurisdiction over the Metropolis of Kiev. In the beginning of the 19th century, Kiev lost its Metropolitan status and became a regular diocese of the Russian Orthodox Church. Only in the beginning of the 20thcentury, during the time of the Ukrainian revolution were efforts made to create an independent Church of Ukraine. In 1919 the autocephaly was announced, but the Patriarchate of Constantinople did not recognize it. . The structure of this Church was soon to be liquidated and it was restored again after the second world war at the time when Hitler occupied the Ukraine. In 1992, after the dissolution of the Soviet Union, when Ukraine gained its independence, the Metropolitan of Kiev requested that the Orthodox Church of Ukraine becomes autocephalous but his request was rejected by the Patriarchate of Moscow. Until 2018 the Patriarchate of Kiev and the autocephalous Church remained unrecognized and thus considered schismatic. In 2018 the Ecumenical Patriarchate of Constantinople looked into the matter and on 5thJanuary 2019, the Orthodox Church of Ukraine received it’s tomos of autocephaly from Constantinople. The Patriarchate of Moscow opposed the decision of Constantinople and as a result refused to perform a common Eucharist with the new Church of Ukraine and with the Patriarchate of Constantinople.